A potential therapeutic neutralization monoclonal antibody specifically against multi-coxsackievirus A16 strains challenge. Issue 10 (3rd October 2019) - Du, Ruixiao; Mao, Qunying; Hu, Yalin; Lang, Shuhui; Sun, Shiyang; Li, Kelei; Gao, Fan; Bian, Lianlian; Yang, Ce; Cui, Bopei; Xu, Longfa; Cheng, Tong; et al.
ABSTRACT: Coxsackievirus A16 (CA16) has caused worldwide epidemics of hand, foot and mouth disease (HFMD), particularly in infants and pre-school children. Currently, there are no vaccines or antiviral drugs available for CA16-associated disease. In this study, a CA16-specific monoclonal antibody (MAb) NA11F12 was derived with an epidemic CA16 strain (GenBank no. JX127258). NA11F12 was found to have high cross-neutralization activity against different CA16 subgenotypes but not EV71 using RD cells. The neutralizing titers of NA11F12 ranged from 1:1024 to 1:12288 against A, B1, B2 and C subgenotypes of CA16 and was less than 8 against EV71 strain. In the neonatal mouse model, a single treatment of NA11F12 showed effective protection with a dose- and time-dependent relationship against lethal challenge by CA16 strain (GenBank no. JX481738). At day 1 post-infection, administering more than 0.1 μg/g of NA11F12 could protect 100% newborn mice from mobility and mortality challenged by CA16. With dose of 10 μg/g of NA11F12, a single administration fully protected mice against CA16-associated disease within 4 days post-infection. And there were 80% and 60% mice protected by administering NA11F12 at day 5 post-infection and day 6 post-infection when the control mice had shown clinical symptoms for 1- and 2-day, respectively. Immunohistochemical and histological analysis confirmed that NA11F12 significantly prohibited CA16 VP1 expression in various tissues and prevented CA16-induced necrosis. In conclusion, a CA16-specific MAb NA11F12 with high cross-neutralization activity was identified, which could effectively protect lethal CA16 challenge in mice. It could be a potential therapeutic MAb against CA16 in the future.